Overdeterminacy and endogenous cycles : Trygve Haavelmo's business cycle model and its implications for monetary policy - André K. Anundsen; Tord S. H. Krogh; Ragnar Nymoen; Jon Vislie (University of Oslo, Department of Economics, 2011)
This paper presents the business cycle model that Trygve Haavelmo developed as part of his research program in macroeconomic and monetary theory. Driven by a mismatch between the marginal return to capital and the rate of return required by capital owners, this model generates endogenous cycles. The theory leads to a distinct analysis of the scope and limitations of monetary policy. A main message of the model is that care should be taken when conducting 'autonomous' monetary policy and that special emphasis should be put on the soundness of nancial markets. Adopting a strict nominal anchor as the main objective of monetary policy might generate imbalances in the capital market.
Keywords: E22; E32; E44; E52; 330; investments; business cycles; monetary policy